CONTRIBUTIONS TO THE CICADOMORPHA AND FULGOROMOR-PHA (HEMIPTERA) FAUNA OF TURKISH THRACE REGION - AHMET Dursun; Meral Fent (Trakya University Journal of Natural Sciences, 2016)
Specimens of Cicadomorpha and Fulgoromorpha were collected in different localities in Thrace region of Turkey during the spring and summer periods of 2014. The collected samples were evaluated taxonomically and Eupelix cuspidata (Fabricius, 1775) (Cicadellidae) from Cicadomorpha and Euides basilinea (Germar, 1821) (Delphacidae), Metcalfa pruinosa (Say, 1830) (Flatidae), Scorlupella discolor (Germar, 1821) (Issidae), Ricania hedenborgi Stål, 1865 (Ricaniidae) and Tettigometra laeta Herrich-Schäffer, 1835 (Tettigometridae) from Fulgoromorpha were recorded for the first time in the study region. E. cuspidata have been only known from Anatolia so far. S. discolor was recorded in various localities, and T. laeta and the exotic species M. pruinosa were recorded only in one locality in Anatolia. Records of E. basilinea was given from Turkey without any data on the locality. Distributions of the all recorded species in Turkey and inside the Palaearctic Region were given.